CLOUD INFRASTRUCTURE SECURITY AT DIFFERENT LAEVELS - Kavita M. Sunchu; Prof. Dhainje P.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
Cloud Computing is the collection of different types of hardware and software which delivers many services to the end-user over a network (typically the Internet). With cloud computing, users can access files and use applications from any device that can access the Internet. Now a day’s cloud computing becomes more popular due to its few important attributes:multitenancy (single instance of software is used to run a service for multiple clients), massive scalability, elasticity, pay-per-use, and self-provisioning of resources. Cloud computing also delivers different types of services like Software-as-a-Service (SaaS), Platform-as-a-Services (PaaS) and Infrastructure-as-a-Services (IaaS). The current paper discussed infrastructure security at different levels:such as Application level, Host level and network level